(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
There are a lot of claims about the term “Just in Time” concept and its appropriateness in teaching process. Some researchers even doubt about the target term being a concept at all. The current article demonstrates the utilization of the “Just in Time concept” in ESP teaching process and its drawbacks as well. Not a secret, the profession of Economist requires the specific skills and abilities, due to the importance of data they provide to be correct and detailed. Moreover, the experts should be aware of international state of economy, of developed countries, so that they are able to compare, modify collect data. The main notion of the concept, which will be focused on within the article, is to encourage future economists to develop their cognitive skills. Aligned with the advantages some drawbacks will be pointed out, and discussed based on literature review.